2021
DOI: 10.1038/s41598-021-02093-6
|View full text |Cite
|
Sign up to set email alerts
|

Variability in biopsy quality informs translational research applications in hepatocellular carcinoma

Abstract: In the era of precision medicine, biopsies are playing an increasingly central role in cancer research and treatment paradigms; however, patient outcomes and analyses of biopsy quality, as well as impact on downstream clinical and research applications, remain underreported. Herein, we report biopsy safety and quality outcomes for percutaneous core biopsies of hepatocellular carcinoma (HCC) performed as part of a prospective clinical trial. Patients with a clinical diagnosis of HCC were enrolled in a prospecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…It is important to understand the quality of tissue sample needed for different tests as the tissue requirements can vary from one molecular assay to another. A recent analysis of biopsies performed for 50 patients with hepatocellular carcinomas for genetic, proteomic, and metabolomic profiling were evaluated for the quality thresholds of the biopsy samples [ 292 ]. In total, 76.8% of the biopsies were found to be adequate for next-generation sequencing and 41.1% of the biopsies were found to be adequate for proteomic/metabolomic profiling [ 292 ].…”
Section: Applications In Interventional Oncologymentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to understand the quality of tissue sample needed for different tests as the tissue requirements can vary from one molecular assay to another. A recent analysis of biopsies performed for 50 patients with hepatocellular carcinomas for genetic, proteomic, and metabolomic profiling were evaluated for the quality thresholds of the biopsy samples [ 292 ]. In total, 76.8% of the biopsies were found to be adequate for next-generation sequencing and 41.1% of the biopsies were found to be adequate for proteomic/metabolomic profiling [ 292 ].…”
Section: Applications In Interventional Oncologymentioning
confidence: 99%
“…A recent analysis of biopsies performed for 50 patients with hepatocellular carcinomas for genetic, proteomic, and metabolomic profiling were evaluated for the quality thresholds of the biopsy samples [ 292 ]. In total, 76.8% of the biopsies were found to be adequate for next-generation sequencing and 41.1% of the biopsies were found to be adequate for proteomic/metabolomic profiling [ 292 ]. The results of this study demonstrated the difficulty in obtaining adequate biopsies for complete profiling and the need for non-destructive point of care tests to confirm the adequacy of biopsies.…”
Section: Applications In Interventional Oncologymentioning
confidence: 99%
“…27 Many biomarker studies are also never published and so have limited contributions to the advancement of science. 28 There is also variability in the quality of tissue collected in research biopsies, which limits their utility in answering scientific questions. 29 At NCI-designated cancer centers, clinical trials must undergo formal scientific review prior to IRB review.…”
Section: E R H E R Hmentioning
confidence: 99%
“…Further, while there may be value to a single biopsy for molecular characterization, some studies seek multiple samples despite little evidence that serial biopsies generate critical scientific insights or impact drug development 27 . Many biomarker studies are also never published and so have limited contributions to the advancement of science 28 . There is also variability in the quality of tissue collected in research biopsies, which limits their utility in answering scientific questions 29 .…”
Section: Ethical Concerns With Nonintegral Research Biopsiesmentioning
confidence: 99%
“…Currently, most health centres can only provide Formalin-Fixed Paraffin-Embedded (FFPE) samples due transport and storage limitations 8,16 . Additionally, the unknown tumor fraction in FF samples poses a degree of uncertainty, since a low tumor fraction in the homogonized sample limits classification 17 . In FFPE samples, histopathological staining can be performed, so the tumor fraction is not only known but can be selectively enriched for analysis 18 .…”
mentioning
confidence: 99%